Co-pyrolysis and co-gasification of biomass and polyethylene: Thermal behaviors, volatile products and characteristics of their residues. Issue 6 (December 2019) - Fan, Honggang; Gu, Jing; Hu, Shuangqing; Yuan, Haoran; Chen, Yong
Abstract: Co-pyrolysis and co-gasification of biomass and plastics could be a promising method to alleviate environmental pollution and provide renewable energy. In this paper, co-pyrolysis and co-gasification of eucalyptus wood (EW) or rice straw (RS) with polyethylene (PE) were investigated by a thermogravimetric analyzer coupled with a Fourier transform infrared spectrometer (TG-FTIR) and a scanning electron microscope coupled with energy-dispersive spectroscopy (SEM/EDS). Results showed that the pyrolysis behaviors were characterized by two stages. The first stage was the decomposition of EW and RS, and the second stage primarily consisted of the degradation of PE. The gasification exhibited a third stage for the reaction of products with CO2 . A synergistic effect was presented in the pyrolysis and gasification of biomass with PE, and it could have a positive effect on the decomposition of biomass. Compared to individual pyrolysis and gasification, co-pyrolysis and co-gasification generated no new substances, but the yield of some products was changed in these processes. In co-pyrolysis, the decomposition of biomass was promoted. In co-gasification, the production of CH4, CO and oxygenated compounds was inhibited, while the reaction to generate H2 O was promoted. Gasification and the addition of PE both increased the carbon content and reduced the oxygen content of volatile products. Additionally, more metal elements could be deposited in residues when PE was added. Highlights: The differences between co-pyrolysis and co-gasification of biomass with polyethylene were studied. A positive effect was observed in the pyrolysis and gasification of biomass with the addition of polyethylene. The generation of H2 O was promoted in co-gasification. More metal elements could be deposited in residues when PE was added in co-pyrolysis and co-gasification.